The Cambridge Introduction to Edgar Allan Poe - Fisher, Benjamin F (Cambridge University Press, 2013)
This book is aimed at advanced high school and lower-level college/university students. It consists of chapter 1, “Life,” in which the mythologies (often quite negative) that have grown up around Poe the person are avoided in favor of a factual account. Chapter 2, “Works,” provides coverage of Poe’s works and their place in the literature of the world. After all, what initially gained Poe widespread attention was his critical writings, an irony since during his teens and early twenties he intensely wanted to be regarded as a poet